En el código del trabajo se debe incorporar medidas de protección para las personas con capacidades especiales con la finalidad de evitar la discriminación y el mal trato para estos trabajadores - López Armijos, Violeta María (2014)
Discrimination, in my view, is the action of giving inferior treatment in a group, some of its members for a particular reason, be it race, religion, sex, or for the present case, the disabled, the assets and liabilities of the same subject. Therefore, it must be clear that discrimination exists as long as someone feels discriminated against; without the perception of the sufferer cannot speak of discrimination, so the voice of discrimination has to rise as a prerequisite, sine qua non, to get to consider the corresponding phenomenon and, if necessary, to bring you near appropriate remedies; hence the disabled people themselves believe that there is a type of discrimination based on rejection, fear and ignorance, which is present in almost all activities of daily living. It is true that the stereotypes that people have against the disabled do not pose an immediate rectification of personal behavior or a parallel feeling of discrimination, but it is clear that the support of the system, it should be a rule to the case at hand which is needed, is critical on the road to equality and pluralistic coexistence, for that, I encourage all who perceive an inferior treatment by reason of their disability, in any of the public, it must also contribute to achieving win the fight against the discrimination that disabled people themselves admit as necessary, where they are increasingly aware of their right to equality and nondiscrimination is something that must fight and not a free grant of society the living, however it all and the laws that protect all people with disabilities natural or accidental nature, are people who have rights and obligations and to meet demand. Discrimination on the grounds of disability has been experienced, to varying degrees, in recent times because this is not just directed to the disabled, but other vulnerable members of society such as black, indigenous race, montubio etc. by place of origin, customs, by the company to which they belong, in the end these are all the factors with which the discrimination is directed.